각막 콜라겐 교차결합술, 스마일수술 병합수술과 단독 스마일수술의 초기 임상성적 비교 - 김부기(Bu ki Kim), 문수정(Su joung Mun), 최현태(Hyun tae Choi), 양영훈(Young hoon Yang), 정영택(Young taek Chung) (Daihan angwa haghoi jabji, 2017)
목적: 각막 콜라겐 교차결합술과 스마일수술을 동시에 시행 받은(엑스트라스마일수술) 환자와 스마일수술을 단독으로 시행 받은 환자의 임상결과를 비교해 보고자 하였다. 대상과 방법: 엑스트라스마일수술을 시행 받고 6개월 이상 경과관찰이 가능하였던 환자 15명 30안과 같은 기간 동안 스마일수술만을 시행 받은 환자 중 6개월 이상 경과관찰이 가능하였던 환자 중 임의 추출방식으로 15명 30안을 대조군으로 선정하여서 후향적으로 연구하였는데, 나안시력, 최대교정시력, 효율성지수, 안전성지수, 각막 고위수차 등을 비교하였다. 결과: 술 전 두 군은 구면렌즈대응치, 중심부 각막두께, 예상 잔여각막두께, 수술 시 광학부 직경에서 차이를 보였으나(p<0.001), 술 후 6개월의 경과관찰 기간 동안 나안시력과 최대교정시력은 두 군 간 차이를 보이지 않았다. 효율성지수는 엑스트라스마일군에서 술 후 6개월에 0.97 ± 0.16, 대조군에서 1.05 ± 0.17로 두 군 간 유의한 차이를 보였고(p=0.044), 안전성지수는 경과관찰 기간 동안 두 군 간 유의한 차이를 보이지 않았다. 각막 총 고위수차의 root mean square 값이 엑스트라스마일군에서 2.59 ± 0.56, 대조군에서 2.02 ± 0.41로 유의한 차이를 보였고(p<0.001), 그리고 술 전후를 비교하였을 때 두 군 모두에서 구면수차와 수평코마수차가 유의하게 증가하였다. 엑스트라스마일군에서 술 후 6개월째 20%에서 각막혼탁이 관찰되었고, 각막확장증은 두 군 모두에서 나타나지 않았다. 결론: 엑스트라스마일수술은 스마일 단독 수술과 비교해서 만족할 만한 초기 임상성적을 보였고, 술 전 각막두께가 얇거나 교정량이 많은 경우 고려할 수 있는 수술적 치료이다. 그러나 술 후 발생할 수 있는 각막혼탁에 대해서 유의해야 한다. Purpose: To compare the clinical outcome of combined small incision lenticule extraction and collagen cross-linking (SMILE Xtra) with SMILE. Methods: This study included 30 eyes from 15 patients who had undergone SMILE Xtra and a random sample of 30 eyes from 15 patients receiving SMILE alone during the same period. We obtained the following parameters from all patients: uncorrected (UDVA) and corrected distance visual acuity (CDVA), spherical equivalent (SE), efficacy and safety index, and corneal high-order aberrations. Results: The SMILE Xtra group had higher preoperative SE and thinner central corneal and residual stromal bed thickness and optic zone diameter compared to the control group (p < 0.001). At 6 months, there was no significant difference in UDVA or CDVA between the two groups. The efficacy indices were 0.97 ± 0.16 and 1.05 ± 0.17 in the SMILE Xtra and control groups, respectively (p = 0.044), and there was no significant difference in safety index between the two groups during the follow-up period. Total corneal high-order aberrations numbered 2.59 ± 0.56 and 2.02 ± 0.41 in the SMILE Xtra and control groups, respectively (p <0.001), and there was significant increase in spherical aberration and horizontal corneal aberration in both groups compared to preoperative results. Corneal haze was observed in 20% of eyes in the SMILE Xtra group, and no complication such as corneal ectasia was observed during the follow-up period. Conclusions: SMILE Xtra had good early clinical outcome compared to SMILE alone. It appears that SMILE Xtra can be a good modality when the cornea is thin or SE is high. However, postoperative corneal haze should be considered. KCI Citation Count: 0